2018
DOI: 10.1002/ana.25313
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of no evidence of progression or active disease (NEPAD) in patients with primary progressive multiple sclerosis in the ORATORIO trial

Abstract: ObjectiveNo evidence of progression or active disease (NEPAD) is a novel combined endpoint defined by the absence of both progression and inflammatory disease activity in primary progressive multiple sclerosis (PPMS). In the placebo‐controlled phase III ORATORIO study (NCT01194570), we investigated the effect of ocrelizumab on this comprehensive outcome and its components in a post‐hoc analysis.MethodsThe proportion of patients with NEPAD (no evidence of progression [NEP; no 12‐week confirmed progression of ≥1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 25 publications
1
18
0
1
Order By: Relevance
“…Recent advances in the treatment of progressive forms of MS emphasized the importance of reliable and comprehensive measures of disease progression, as EDSS has limited ability to reliably capture change in functioning in a range of domains . Therefore, a composite measure including upper limb function, ambulation speed as well as EDSS was developed to measure disability progression . The results of the present study have shown that an EP score >13 which uses VEMPs and tSSEPs increases the likelihood for progression measured with this composite measure.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Recent advances in the treatment of progressive forms of MS emphasized the importance of reliable and comprehensive measures of disease progression, as EDSS has limited ability to reliably capture change in functioning in a range of domains . Therefore, a composite measure including upper limb function, ambulation speed as well as EDSS was developed to measure disability progression . The results of the present study have shown that an EP score >13 which uses VEMPs and tSSEPs increases the likelihood for progression measured with this composite measure.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, T25FW and 9HPT were performed on the baseline visit and after 2 years of follow‐up. For better insight into disease progression, a composite measure consisting of EDSS, T25FW and 9HPT was used to evaluate evidence of progression . The evidence for progression was defined as the presence of SAD measured by the EDSS as described above, or evidence of ≥20% progression on hand/arm function as measured by the 9HPT, and/or evidence of ≥20% progression on ambulation as measured by the T25FW.…”
Section: Methodsmentioning
confidence: 99%
“…Although the effect of ocrelizumab in PPMS was only modest, it was sustained, and patients in the extension study initiating ocrelizumab between 3-5 years earlier had significant and sustained reductions in disability progression compared with patients switching from placebo after 144-240 weeks (45). In post-hoc analyses, ocrelizumab increased 3-fold the proportion of PPMS patients achieving a novel combined measure of NEPAD (no evidence of progression or active disease), defined by the absence of both progression and inflammatory disease activity, which may represent a measure of disease control that is sensitive and meaningful in patients with PPMS (46). Ocrelizumab also reduced the progression of upper limb disability in more disabled or older patients, a finding that set the stage for a larger ORATORIO-HAND study, which is intended to further investigate the efficacy of ocrelizumab in improving upper limb function (47).…”
Section: Ms Therapies Targeting B Cellsmentioning
confidence: 99%
“…In the phase 3 RCT in PPMS (ORATORIO), we considered only the placebo arm for the longitudinal analysis because the time-to-event analysis was modified by the experimental drug 13 . Since the number of 24-week confirmed EDSS progression events per MS subtype in the placebo group was too small (<23 events per subtype on average) to provide statistically reliable results, we defined an event as ≥20% increase in the averaged 9 Hole-Peg Test time between two hands, following Wolinsky et al's recommendation 32 .…”
Section: ) Testing Sustain On the External Unseen Datasetmentioning
confidence: 99%